2018
DOI: 10.1002/jcb.26674
|View full text |Cite
|
Sign up to set email alerts
|

Temozolomide analog PMX 465 downregulates MGMT expression in HCT116 colorectal carcinoma cells

Abstract: The efficacy of temozolomide (TMZ) treatment for cancers is currently limited by inherent or the development of resistance, particularly, but not exclusively, due to the expression of the DNA repair enzyme O6-methylguanine-DNA methyltransferase (MGMT) in a significant proportion of tumors. We have found that TMZ analog C8-methyl imidazole tetrazine (PMX 465) displayed good anticancer activity against the colorectal carcinoma HCT116 cells which are MGMT-overexpressing and mismatch repair (MMR)-deficient. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…None of the chemotherapy agents typically used as part of LCRT or TNT are true directly alkylating agents. It is possible that any substantially increased benefit for MGMTh patients from the addition of Temozolomide or other direct alkylating agents may be in the definitive setting combined with newer therapies [49] , [50] .…”
Section: Discussionmentioning
confidence: 99%
“…None of the chemotherapy agents typically used as part of LCRT or TNT are true directly alkylating agents. It is possible that any substantially increased benefit for MGMTh patients from the addition of Temozolomide or other direct alkylating agents may be in the definitive setting combined with newer therapies [49] , [50] .…”
Section: Discussionmentioning
confidence: 99%
“…However, oxaliplatin treatment had less inhibitory effect in mice bearing HCT116 tumor cells (Figure S2A-C). Several studies have shown that HCT116 is an MMR-deficient cell line while SW480 is an MMR-proficient cell line, and that loss of MMR leads to increased adaptive variability and chemoresistance in CRC [10,[16][17][18]. Therefore, we detected the protein and mRNA expression of functional proteins in MMR.…”
Section: Mmr Is Inhibited In C Tropicalis-induced Crc Chemotherapy Resistancementioning
confidence: 99%